Brain-derived neurotrophic factor facilitates TrkB down-regulation and neuronal injury after status epilepticus in the rat hippocampus - Unsain, Nicolas (2009)
Brain-derived neurotrophic factor (BDNF) is involved in many aspects of neuronal biology and hippocampal physiology. Status epilepticus (SE) is a condition in which prolonged seizures lead to neuronal degeneration. SE-induced in rodents serves as a model of Temporal Lobe Epilepsy with hippocampal sclerosis, the most frequent epilepsy in humans. We have recently described a strong correlation between TrkB decrease and p75ntr increase with neuronal degeneration (Neuroscience 154:978, 2008). In this report, we report that local, acute intra-hippocampal infusion of function-blocking antibodies against BDNF prevented both early TrkB down-regulation and neuronal degeneration after SE. Conversely, the infusion of recombinant human BDNF protein after SE greatly increased neuronal degeneration. The inhibition of BDNF mRNA translation by the infusion of antisense oligonucleotides induced a rapid decrease of BDNF protein levels, and a delayed increase. If seizures were induced at the time endogenous BDNF was decreased, SE-induced neuronal damage was prevented. On the other hand, if seizures were induced at the time endogenous BDNF was increased, SE-induced neuronal damage was exacerbated. These results indicate that under a pathological condition BDNF exacerbates neuronal injury.